Efeito do ensino de sinônimos sobre a compreensão de textos - Aran, Marineide Aquino de Souza (Universidade Federal de São Carlos, 2016)
The ultimate goal of learning how to read is to understand the information present in a text and variables involved in reading with understanding have been widely studied. This paper aims to investigate whether teaching synonyms of words that make up the main structure of texts contributes to an increase in text comprehension. These words are also part of stories utilized in standardized teaching procedures. The participants in this study were 20 typically developing children, aged from 8 to 10 years old, pupils from first to fifth grade of a primary public school in the State of São Paulo. They showed high scores when reading single words, but a poor performance in understanding texts. The control group underwent a procedure for learning text comprehension. The experimental group underwent the same procedure as the control group but it was also taught synonyms. Performance in text comprehension was evaluated both before and after the interventions for both groups. The analysis of baseline and post intervention data for all participants was done through the T test of matched samples and the Mann-Whittman test was used for comparing data between groups. Posttest results don’t show any statistically significant difference between the performances of the experimental and control groups, which suggests that teaching synonyms had no effect on text comprehension. Considering the performance of all participants in the pre and posttests, regardless of which intervention the participant received, there is a significant difference between them, which points out the effectiveness of the teaching procedure to increase text comprehension.
Keywords: Compreensão de textos; Ensino de sinônimos; Crianças; Text comprehension; Vocabulary; Children; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO ENSINO E DA APRENDIZAGEM::ENSINO E APRENDIZAGEM NA SALA DE AULA